Transcranial direct current stimulation in patient with J wave syndrome and implantable cardioverter defibrillator. Issue 5 (28th January 2022) - Samani, Susan; Samimi, Sahar; Mollazadeh, Reza; Mehrpour, Masoud
Abstract: J wave syndrome is a spectrum of proarrhythmic disorders including Brugada syndrome and early repolarization syndrome (ERS), that are prone to ventricular fibrillation and sudden cardiac death (SCD). In this case report we present a patient with ERS and aborted SCD complicated with cognitive impairment. We also investigated whether performing transcranial direct current stimulation to target his cognitive impairment, interfered with the function of his implantable cardioverter defibrillator.